Passive Radiative Cooling Film Design via Transfer Matrix Modeling and Genetic Algorithm Optimization - Zhu, Weijin (International Journal of Computer Science and Information Technology, 2026)
This paper proposes a unified modeling approach integrating optical modeling, thermal radiation calculations, and energy balance analysis for the passive radiative cooling performance of polydimethylsiloxane (PDMS) films. Based on film interference theory and the transfer matrix method, a quantitative relationship between film thickness and spectral emission characteristics is established, enabling systematic evaluation of emission performance under thermal equilibrium conditions. Model results reveal the critical influence of thickness modulation on mid-infrared radiation capability, providing explicit physical guidance for structural design. Building upon this, a genetic algorithm is introduced to perform global joint optimization of material combinations and layer thickness parameters in multilayer film structures, enabling synergistic control over solar reflection and atmospheric window radiation. Optimization results demonstrate that this approach significantly enhances net cooling performance at reduced structural thickness, exhibiting excellent versatility and scalability. It provides a unified modeling and optimization framework for designing radiative cooling films and related photothermal control structures.